Safety and efficacy of pediatric liver transplantation in Saudi Arabia - Mehder, Ashraf Saeed; Saati, Roaa Abdullah; Alhamdani, Linah Abdulrahman; Qari, Wadah Kamal; Alqurashi, Rawan Mohammad; Alkidaiwi, Shahad Sameer; Alsubhi, Arwa Ayash; Alosaimi, Ashwaq Dakhel; Alsharif, Anfal Jameel; Bahareth, Amna Ali (International Journal Of Community Medicine And Public Health, 2022)
Evidence shows that liver transplantation is a good management choice for pediatric patients with severe hepatic disorders. In addition, the approach can be used for managing different hepatic disorders, including metabolic and familial ones. Therefore, liver transplantation is indicated and should be urgently conducted to intervene against further deterioration in the health status of the affected patients and enhance their prognosis. Various investigations in the literature validated the efficacy of the modality for different age groups, although many of them reported the incidence of different related complications. In Saudi Arabia, not many studies reported the safety and efficacy of liver transplantation for pediatric patients. The present literature review provided insight regarding the safety and efficacy of the procedure for this population group. We can conclude that liver transplantation in pediatric settings is a safe and productive approach that can be successfully conducted with a favorable prognosis. Moreover, it has been shown that living-related liver transplantation is more favorable than cadaveric-related liver transplantation in these settings, especially when there is a graft shortage, as reported in Saudi Arabia. Despite the favorable outcomes, further reports are still needed for validating the current evidence.